Social Media and Marital Relations among Married Women: A Scoping Review and Islamic Ethical Analysis Using the Maqasid al-Sharia Framework - Zara Muhammad Jajere; Uthman Mohammed Mustapha Kannike (Goodwood Publishing, 2026)
Purpose: This study aims to examine how social media use influences marital relations among married women and interpret recurring relational patterns through the maq??id al-shar??a framework, integrating empirical research with Islamic ethical analysis. Research Methodology: A scoping review guided by the PRISMA-ScR framework was conducted using major academic databases. Peer-reviewed empirical and theoretical studies that addressed social media and marital dynamics were included. Data were systematically extracted and analyzed using thematic synthesis. The identified themes were subsequently interpreted through the five classical maq??id objectives: preservation of religion, life (emotional well-being), intellect, lineage (family integrity), and property (economic trust). Results: Five dominant themes emerged: emotional boundary reconfiguration, surveillance and jealousy, social comparison, gendered moral scrutiny, and digital economic participation. The findings indicate that social media functions as a relational amplifier, intensifying the pre-existing dynamics of trust, insecurity, and negotiation rather than serving as a deterministic cause of marital instability. Maq??id-based analysis demonstrates ethical convergence between empirical findings and Islamic objectives concerning emotional stability, moral conduct, rational discernment, family cohesion, and economic transparency. Conclusions: Social media reshapes marital interactions structurally and symbolically, requiring contextual and ethically grounded evaluations. The maq??id framework provides a structured lens for assessing digital intimacy within marriage, emphasizing welfare, justice, and relationship accountability. Limitations: This review is limited to English-language publications and heterogeneous methodologies without a quantitative effect-size assessment. Contribution: This study advances interdisciplinary scholarship by bridging digital sociology and Islamic ethical reasoning and offering a structured normative framework for faith-sensitive digital literacy and marital counseling.